Inclusive career counseling challenges for students with disabilities in higher education - Nur Atiqah Abdullah; Samsiah Jayos (Institute of Advanced Engineering and Science, 2026)
The number of students with disabilities (SWDs) in Malaysian higher education is increasing, yet inclusive career counseling remains underexplored. This study investigates the challenges faced by counselors in supporting SWDs’ career development and highlights practical strategies for improvement. Guided by the planned happenstance theory (PHT), qualitative data were collected through semi-structured interviews with five counselors across different institutions in Sarawak. Thematic analysis revealed four key challenges: communication barriers, limited resources, lack of specialized training, and client dependency. Counselors recommended targeted training, stronger industry collaborations, and improved supervision practices. The study contributes to inclusive education discourse by providing context-specific insights and aligning with sustainable development goal 8 (SDG8), emphasizing the importance of equitable access to career support services for SWDs in higher education.